Effect of Altered Prior Knowledge on Passage Recall - Langer, Judith A.; Nicolich, Mark ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
A study was conducted to determine: (1) the relationships between prior knowledge and passage recall; (2) the effect of a prereading activity (PReP) on available knowledge; and (3) the effect of the PReP activity on total comprehension scores. The subjects were 161 sixth grade students from a middle class suburban Long Island, New York, public school district, classified as high-, average-, or low-achieving readers. Two passages were selected from a sixth grade social studies text, from which three key words were chosen as memory probes for free association. Twenty multiple choice questions were prepared for each passage as comprehension criteria. The subjects were divided into four experimental conditions, with different combinations of free association, PReP, motivation, distractor, text, and questioning activities. Findings indicated that the PReP activity significantly raised the prior knowledge level, and may also have had some generalized effect on comprehension. This was particularly evident for the on-level group where the opportunity to "think through" relevant knowledge has the most effect on comprehension. (HTH)
ERIC Note: Not available in paper copy due to marginal legibility of original document. For related document see CS 005 788.
Educational level discussed: Grade 6.
Educational level discussed: Intermediate Grades.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Advance Organizers; Grade 6.; Intermediate Grades; Prior Learning; Reading Comprehension; Reading Readiness; Reading Research; Recall (Psychology); Free Associations -- Prereading Activities; Schema Theory; Reports, Research